The Disks In Scorpius–Centaurus Survey (DISCS). I. Four Newly Resolved Debris Disks in Polarized Intensity Light - Justin Hom; Thomas M. Esposito; Katie A. Crotts; Gaspard Duchêne; Jennifer Patience; Johan Mazoyer; Robert J. De Rosa; Christine H. Chen; Paul Kalas; Bruce Macintosh; Brenda C. Matthews (The Astronomical Journal)
The presence of infrared excesses around stars directly correlates with spatially resolved imaging detections of circumstellar disks at both millimeter and optical/near-infrared wavelengths. High-contrast imagers have resolved dozens of circumstellar disks with scattered light polarimetric imaging. Many of these detections are members of the Scorpius–Centaurus OB association, demonstrating it to be a rich sample for investigating planetary system architectures and planet–disk interactions. With the goal of expanding the sample of directly imaged debris disks in Scorpius–Centaurus, we conducted the Disks In Scorpius–Centaurus Survey, leveraging knowledge of high-IR excesses and the power of high-contrast polarimetric differential imaging. In combination with the GPIES polarimetric disk survey, we observe seven new Scorpius–Centaurus targets to achieve a 60% complete survey of debris disks with IR excesses exceeding 2.5 × 10 ^−4 , resolving four new debris disks. HD 98363, HD 109832, and HD 146181 are resolved for the first time, and HD 112810 is resolved for the first time in polarized intensity. We identify morphological structures that may be indications of planet–disk interactions. We place the systems in the greater context of resolved debris disks, identifying order of magnitude differences in scattered light contrast for a given IR excess, implying gaps in our understanding of the smallest and largest dust grains of a system. We conclude that while thermal emission measurements are correlated with scattered light detection, they poorly predict the magnitude of scattered light brightness. We also establish Scorpius–Centaurus debris disks as critical benchmarks in understanding the properties of disks in the scattering regime.